Regal Jumping Spider, Phidippus regius C. L. Koch (Arachnida: Salticidae) - Glavis B. Edwards (EDIS)
Except for two pantropical species (Edwards 1979), the jumping spider most frequently encountered in Florida is Phidippus regius C.L. Koch. This species is aptly named in terms of its size, as it is the largest jumping spider in eastern North America. The species is found in the southeastern U.S., the Greater Antilles, and the Bahamas, but is most common in peninsular Florida. This document is EENY-152 (originally published as DPI Entomology Circular 223), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2000.